The General Santos Museum and Convention Center redefining convention destination experience through integrating city context - Cariaga, Adrian Paul R.
Apart from being known as the Tuna Capital of the Philippines, General Santos City boasts itself for its rich and diverse culture. With the plethora of different types of events that happens in the city year-round, it places itself on a challenge to establish events facilities to cater the growing demand. This study aims to conceptualize a design project that redefines convention destination experience in order to solve the prevalent issue of lack of event spaces in the city and respond to the call of elevating convention experience. The study integrated the city’s context as an innovative tool through spaces that showcases the thriving tourism and fishing industries of the city and it assimilated relevant theories and design concepts such as learning and interaction strategies to further innovate it. Overall, the results of the study highlighted some of the many outcomes that can be expected in the facilitation of the said project such as greater network cooperation, adding depth to public awareness, and a projected boost on the city and regional development.